Pattern of utilization of benzodiazepines in patients with hypertension: A pilot study - Divac Nevena; Veljković Slavomir; Nešić Zorica; Stojanović Radan; Bajčetić Milica; Vasiljević Zorana; Prostran Milica; Samardžić Ranka (Vojnosanitetski Pregled)
Background/Aim. The analysis of drug prescribing in general practice in Serbia showed that the use of benzodiazepines is most frequently associated with hypertension. The aim of this study was to establish the correlation of the characteristics of patients with hypertension to antihypertensive drug therapy, and the intake of benzodiazepines. Methods. A special questionnaire was used for interviewing the patients (n = 171) chronically treated for hypertenson. Statistical tests used were χ2-test and Student's t-test. Results. No differences were noted in terms of age, gender, education, body weight, smoking habits and blood pressure (155±4.9/100±2.7 mmHg vs. 160±2.2/105±3.7 mmHg), between the group I (antihypertensive drugs+benzodiazepines: n = 79), and the group II (antihypertensives only: n = 92). The patients taking benzodiazepines received a lower number of different antihypertensive drugs (2.3±0.09 vs. 2.7±0.10; p < 0.01), but the total antihypertensive drug load was significantly greater than in the group II (2.6±0.10 vs. 1.9±0.15 defined daily doses (DDD)/patient/day; p < 0.01). Benzodiazepines were taken for anxiety (62%) and hypertension (21%), rarely for insomnia, mostly once a day, at bedtime. About half the patients took benzodiazepines regularly for months or years aware of the risk for addiction. Diazepam was used by 82% of the patients. The average daily exposure to benzodiazepines was 0.45±0.05 DDD/patient/day. The drug was bought without prescription in 25% of the patients, and without consulting a physician in 12% of them. Conclusion. The study confirmed a close association of hypertension with the use of benzodiazepines. The frequent use of benzodiazepines in the patients with hypertension might be caused by an inadequate response to antihypertensive drug therapy, besides anxiety and insomnia. The therapeutic efficacy of a long-term use of low doses of benzodiazepines in hypertension requires further investigation.